[INVITED] Self-induced polarization tracking, tunneling effect and modal attraction in optical fiber. (June 2016) - Guasoni, M.; Morin, P.; Bony, P.-Y.; Wabnitz, S.; Fatome, J.
Abstract: In this paper, we report the observation and exploitation of the capability of light to self-organize its state-of-polarization, upon propagation in optical fibers, by means of a device called Omnipolarizer. The principle of operation of this system consists in a counter-propagating four-wave mixing interaction between an incident signal and its backward replica generated at the fiber output thanks to a reflective fiber loop. We have exploited this self-induced polarization tracking phenomenon for all-optical data processing and successfully demonstrated the spontaneous repolarization of a 40-Gbit/s On–Off keying optical signal without noticeable impairments. Moreover, the strong local coupling between the two counter-propagating waves has also revealed a fascinating aspect of the Omnipolarizer called polarization-based tunneling effect. This intrinsic property enables us to instantaneously let "jump" a polarization information onto the reflected signal, long before the expected time-of-flight induced by the round-trip along the fiber span. Finally, we discuss how the concept of self-organization could be generalized to multimode fibers, which paves the way to new important applications in the framework of spatial-mode-multiplexing. Highlights: We exploit the self-organization of light state-of-polarization in optical fibers. The spontaneous repolarization of a 40-Gbit/s RZ optical signal is reported. A polarization-based tunneling effect is experimentally demonstrated. This self-polarization phenomenon is generalized to bimodal fibers.